Sistem Kontrol Otomatis pH Air Pada Hidroponik NFT (Nutrient Film Technique) Untuk Tanaman Pakcoy - Elfira Dyah Ekawati; Ilham Aji Shah Putro; Rahman Hakim Nasrulloh; Misbahul Munir; Novian Patria Uman Putra; Wahyu Setyo Pambudi (STMIK Budi Darma, 2022)
Hydroponics Nutrient Film Technique (NFT) is one of the solutions to plant vegetables in limited land. The method is by flowing water and provide nutritional intake for the plant and control pH level of water. The existing hydroponics system has not used a control system to keep the water pH stable. In order to keep the water pH at 7, a system was established using Arduino Uno and pH Analog DF Robot (SEN0169) pH Sensor. This sensor would read the water pH level as an initial input to determine the additional acid or alkaline solution. This also controlled nutrition solution needed by pakcoy vegetable with a PWM control system on wiper motor functioning as a pump to distribute the acid and alkaline nutrition. Whenever the water pH level was exceeding 8, the wiper motor would start working until the pH level decreased to 6-8, and the alkaline liquid would be added whenever the value of pH level was smaller than 6. To get a water pH at 6-8 would take 2-4 seconds. Keeping the water pH within 6-8 would produce well-grown vegetable, in accordance with the determined reference.